Insight Mahasiswa setelah Mempelajari Filsafat Manusia dari Berbagai Budaya dan Perspektif Global (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Human philosophy is one of the branches of philosophy that explores the essence of human beings, their existence, the values inherent within them, and their relationship with the surrounding environment. In Indonesia, the study of philosophy is often perceived as an abstract subject, distant from everyday life. However, when students are introduced to various cross-cultural philosophical perspectives, a new awareness emerges about what it truly means to be human in a richer and more reflective sense. This study employs a qualitative approach to provide contextual and narrative understanding of students’ experiences in learning human philosophy from diverse cultural and global perspectives. In-depth interviews were conducted with 24 students who had taken the human philosophy course, and the data were analyzed using content analysis to identify key emerging themes. The findings revealed six major themes: developing critical and reflective thinking, understanding cultural diversity, strengthening ethics and morality, increasing self-awareness, making decisions through philosophical perspectives, and fostering tolerance and appreciation for differences. These findings highlight that the study of human philosophy is not only academically relevant but also transformative in shaping students’ character and global awareness. Therefore, it is recommended that human philosophy be taught using a multicultural and global approach, rather than being limited to a single cultural perspective.